Characterization of a maltose-forming α-amylase from an amylolytic lactic acid bacterium Lactobacillus plantarum S21 - Apinun Kanpiengjai (2018)
© 2015 Published by Elsevier B.V. A maltose-forming α-amylase was purified from the culture supernatant of Lactobacillus plantarum S21 cultivated on starch. The enzyme is a monomer with a molecular mass of 95 kDa, its activity is Ca2+-independent, and the optimum of amylase activity was found at pH 5.0 and 45 °C. A remarkable property of the enzyme is its stability over the broad pH range of 4.0-8.0 at 37 °C, where 80-95% of its activity was retained for 12 days and 70-75% was retained for 30 days. The main hydrolysis products from starch, amylose, amylopectin as well as glycogen were maltose (60%) and glucose (38%). The ORF of 2733 bp was confirmed to be an amylase-encoding gene by sequence comparison. The amylase gene encodes a protein of 910 amino acids including a signal peptide sequence. Both the nucleotide and amino acids sequence shared more than 96% identity with the α-amylases from L. plantarum A6, L. manihotivorans LMG18010 and L. amylovorus NRRL B-4540, yet the properties of the enzyme showed some distinct differences to these latter α-amylases and other lactobacillal α-amylases.